Solid Waste and its Relation to the Efficiency of Municipal Services in Ramadi and Fallujah - A Geographical View - Salah A. Mejwal; Natheir S. Al-muhemdi (مجلة جامعة الأنبار للعلوم الإنسانية, 2022)
This research sheds light on the most important services performed by the municipality in the cities of Ramadi and Fallujah associated with solid waste and the problems caused by the efficiency of the performance of municipal services in it requires a detailed study of the uses of land in the city in all sectors, which will lead to know the size, quantity and quality of waste for collection Residential and commercial areas, industrial areas, hospitals, health clinics, parks and parks are among the most urban areas that generate solid waste. Jobs within Ramadi and Fallujah vary considerably due to Activities which are experiencing interference in the residential and commercial activity in both cities and the resulting residue nature related Bhaven sectors.